2023
DOI: 10.3390/agronomy13123083
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Eco-Friendly Bio-Pesticides against the Whitefly Bemisia tabaci (Gennadius) for Sustainable Eggplant Cultivation in Kebbi State, Nigeria

Mustapha Abubakar,
Dhananjay Yadav,
Bhupendra Koul
et al.

Abstract: The eggplant (Solanum melongena L.) is among the vital fruit vegetables cultivated globally for its health and nutritional benefits. However, its production has been hindered by whiteflies (Bemisia tabaci G.) infestation worldwide. This study aims to assess the effect of some bio-pesticides in the control of whiteflies on eggplants under field conditions. The trial consists of seventeen (17) treatments replicated three times for 45 days. From the results obtained, neem leaf extract (60 mL/L) proved more effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…longepedunculata root extracts have demonstrated clear insecticidal activity. The active compounds present in the fractions are involved not only in insect cytotoxicity but also in the neutralization of toxins set up by the insect for its feeding. , Previous research demonstrated that this cytotoxicity was due to a concerted action between the combination of jasmonic acid, salicylic acid, and the pharmacophores of S. longepedunculata, which significantly reduced the population of S.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…longepedunculata root extracts have demonstrated clear insecticidal activity. The active compounds present in the fractions are involved not only in insect cytotoxicity but also in the neutralization of toxins set up by the insect for its feeding. , Previous research demonstrated that this cytotoxicity was due to a concerted action between the combination of jasmonic acid, salicylic acid, and the pharmacophores of S. longepedunculata, which significantly reduced the population of S.…”
Section: Discussionmentioning
confidence: 99%
“…The active compounds present in the fractions are involved not only in insect cytotoxicity but also in the neutralization of toxins set up by the insect for its feeding. 32 , 33 Previous research 34 demonstrated that this cytotoxicity was due to a concerted action between the combination of jasmonic acid, salicylic acid, and the pharmacophores of S. longepedunculata , which significantly reduced the population of S. graminum . Consequently, for aphid feeding, approximately 76 proteins present in its saliva are indispensable, including the expression of the Sg2204 protein, which acts as a suppressor of wheat defense.…”
Section: Discussionmentioning
confidence: 99%